Changing trends of indication of caesarean section - Goyal, Neelam; Pandey, Harshita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Percentage of previous C-section undergoing repeat section is close to 90%-92%, morbidity associated with repeat surgery is bringing an altogether new set of challenges for the upcoming future obstetricians. Object of this study is to highlight high incidence of repeat section required and also growing new indications of C-section due to advanced availability of investigative tools. Methods: Retrospective study of 500 patients who underwent C-section and their indications from April 2019 to July 2019 in Govt Doon Medical college, Dehra Dun. Results: Out of total 500 C-sections carried from April 2019 to July 2019, patients with previous section were found to undergo a repeat C-section in 95% of the cases. Another common indication being oligohydramnios followed by cephalopelvic disproportion and failed induction. Conclusions: After assessing the results it is hereby concluded that the commonest indication of C-section in present time is having a previous C-section, which alarms us to take careful judicious decision in performing primi C-sections in order to prevent patients into entering a vicious cycle of repeat surgeries.